2017
DOI: 10.1111/jocd.12320
|View full text |Cite
|
Sign up to set email alerts
|

Hair loss at injection sites of mesotherapy for alopecia

Abstract: Mesotherapy for androgenetic alopecia may paradoxically induce hair loss and scarring. Proper regulation and monitoring of the use of mesotherapy products for treating hair loss in women, needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…In such a case presented by Kadry et al, the conservative treatment seemed to show no effect; so the surgical removal of the inflamed tissues was selected as the treatment of choice . El‐Komy et al describe a series of three patients, where the prominent histologic feature was not an inflammation of the fat tissue, but rather an inflammatory scarring process with perivascular and perifollicular lymphohistiocytic infiltration and sebaceous gland hyperplasia, as well as a hypertrophy of the perifollicular collagen fibers . The mesotherapy cocktail used in two out of the three cases included dutasteride 0.005% (Mesologica ® ), insulin‐like growth factor‐1 (IGF‐1), basic fibroblast growth factor (bfGf), vascular endothelial growth factor (VEGF), copper tripeptide‐1, multi‐vitamins, amino acids, and minerals (Mesologica MRS Hair ® ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In such a case presented by Kadry et al, the conservative treatment seemed to show no effect; so the surgical removal of the inflamed tissues was selected as the treatment of choice . El‐Komy et al describe a series of three patients, where the prominent histologic feature was not an inflammation of the fat tissue, but rather an inflammatory scarring process with perivascular and perifollicular lymphohistiocytic infiltration and sebaceous gland hyperplasia, as well as a hypertrophy of the perifollicular collagen fibers . The mesotherapy cocktail used in two out of the three cases included dutasteride 0.005% (Mesologica ® ), insulin‐like growth factor‐1 (IGF‐1), basic fibroblast growth factor (bfGf), vascular endothelial growth factor (VEGF), copper tripeptide‐1, multi‐vitamins, amino acids, and minerals (Mesologica MRS Hair ® ) .…”
Section: Resultsmentioning
confidence: 99%
“…El‐Komy et al describe a series of three patients, where the prominent histologic feature was not an inflammation of the fat tissue, but rather an inflammatory scarring process with perivascular and perifollicular lymphohistiocytic infiltration and sebaceous gland hyperplasia, as well as a hypertrophy of the perifollicular collagen fibers . The mesotherapy cocktail used in two out of the three cases included dutasteride 0.005% (Mesologica ® ), insulin‐like growth factor‐1 (IGF‐1), basic fibroblast growth factor (bfGf), vascular endothelial growth factor (VEGF), copper tripeptide‐1, multi‐vitamins, amino acids, and minerals (Mesologica MRS Hair ® ) . The management of this adverse reaction included the prescription of topical minoxidil or the application of intralesional saline injections twice daily at the affected area, combined with a topical melatonin solution .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported patchy hair loss [54] and cicatricial alopecia [55] after the injections. Multifocal scalp abscesses with fat necrosis was also reported [56].…”
Section: Hair Mesotherapymentioning
confidence: 99%